2021
DOI: 10.1002/bab.2109
|View full text |Cite
|
Sign up to set email alerts
|

Domain‐wise differentiation of Mycobacterium tuberculosis H37Rv hypothetical proteins: A roadmap to discover bacterial survival potentials

Abstract: Proteomic information revealed approximately 3,923 proteins in Mycobacterium tuberculosis H 37 Rv genome of which around ∼25% of proteins are hypothetical proteins (HPs). The present work comprises computational approaches to identify and characterize the HPs of M. tuberculosis that symbolize the putative target for rationale development of a drug or antituberculosis strategy. Proteins were primarily classified based on motif and domain information, which were further analyzed for the presence of virulence fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The PDB structures were assessed by employing different in silico methods ( Table 3 ). The crystal structures of the selected M. tuberculosis H 37 Rv proteins (PDB: 7LD8, 4Q4N, 5XE2, 4LJ1, 1TQ8, 4CHG, 5WZ4, 2JAX, 5SV2, 6L2A) [ 44 ] are provided in Figure S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PDB structures were assessed by employing different in silico methods ( Table 3 ). The crystal structures of the selected M. tuberculosis H 37 Rv proteins (PDB: 7LD8, 4Q4N, 5XE2, 4LJ1, 1TQ8, 4CHG, 5WZ4, 2JAX, 5SV2, 6L2A) [ 44 ] are provided in Figure S2 .…”
Section: Resultsmentioning
confidence: 99%
“…After the evaluation of the complete mycobacterial database, 238 proteins were found to belong to the VDA category and 135 proteins had available structural information in the RSCB-PDB databank. In Table 3 , a counteractive study on these proteins led to the determination of 10 proteins, which were Rv1477 , Rv1495 , Rv1566 , Rv2801c , Rv2010 , Rv2623, Rv0554 , Rv1636 , Rv2549c , and Rv2757c [ 44 ]. Rv0554 is an integral part of the menaquinone regulatory operon in Mycobacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted destability value mostly destabilizing on positioned Aspartate into Alanine -0.583 kcal/mol and Aspartate into Glycine -0.379 kcal/mol. Here, Aspartate into Alanine (ASP175ALA) mutation predicted as the most destabilizing and it will destabilize the protein conformation (see Figure 8) [45][46][47]. As many studies already revealed the importance of ATP binding genes in various biological processes of living organisms, thus this work delivers importance of Rv1463 as different and interesting part for understanding the molecular mechanism of survival of this bacterium.…”
Section: Structural Based Mutation-induced Stability Deviationsmentioning
confidence: 94%
“…The Mycobrowser, a Mycobacterial searching browser, was used to obtain the sequence of Universal stress protein Rv1636 from M. tuberculosis . This server is an online database with an extensive library of infectious and non-infectious strains of mycobacterial proteins for extensive genomic and proteomic investigation [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%